Insights into anaerobic digestion of microalgal biomass for enhanced energy recovery - Hasan, M. M.; Mofijur, M.; Uddin, M. N.; Kabir, Zobaidul; Badruddin, Irfan Anjum; Khan, T. M. Yunus (Frontiers in Energy Research, 2024)
This review paper delves into the intricate challenge of transforming microalgal biomass into biofuel through anaerobic digestion, elucidating its significance for sustainable energy production and waste management. Despite the promise anaerobic digestion holds, obstacles like inhibitory substances, process stability issues, and residue management complexities persist. Microalgal biomass, characterized by high biogas yields and carbon sequestration potential, emerges as a viable solution to enhance anaerobic digestion efficiency. Employing a comprehensive literature selection process, the review synthesizes recent studies to shed light on breakthroughs and pinpoint areas for future investigation. Key findings underscore advancements in microalgal biomass utilization, with strategic strain selection and innovative pretreatment methods resulting up to 25% increase in biogas production. Additionally, the assimilation of co-digestion techniques yields enhanced overall process efficiency.Microalgal biomass demonstrates remarkable carbon sequestration capabilities, sequestering up to 60% of CO2 during the anaerobic digestion process. Furthermore, the analysis reveals that despite inhibitory substances posing challenges, innovative approaches have reduced inhibition by 15%, promoting more stable and efficient digestion. Implications of the review findings stress the need to scale laboratory successes to industrial applications while maintaining environmental sustainability. Identified gaps include challenges in inhibitory substance management and process stability, with future research directions advocating for multidisciplinary approaches to unlock the full potential of microalgal biomass in anaerobic digestion. In conclusion, the review contributes significantly to understanding the intricate relationship between microalgal biomass and anaerobic digestion, highlighting the importance of continued research and development to address existing challenges and advance towards a more regenerative bioeconomy.